Developing A Virtual Reality Application of Pathok Negoro Mosque for Digital Conservation - Endang Setyawati; Adwiyah Asyifa; Hendro Trieddiantoro Putro; Mohammad Ischak (Journal of Architectural Design and Urbanism, 2019)
In the last decades, new technologies have been developed and used for digital conservation. Nowadays, virtual reality is becoming an instrument applicable to many areas of science and visual communication. Pathok Negoro Mosque is one of the Javanese Islamic mosque buildings that was built in the 1700s. The building of this mosque still exists. Pathok Negoro Mosque several times has changed the shape and architecture of the building. The mosque was established during the reign of Sultan Hamengku Buwana I, has an extraordinary concept and philosophy. This project was an archiving physical space so they can be digitally preserved. In this paper, we will present the process of the VR app making also describe the benefits and challenges associated with this approach. The method was by research and development by prototyping the building in 3D model, then providing virtual tours in different place and times. This paper will discuss the VR issue focusing on several hardware devices and software platforms for digital content management. This case study allowing a better understanding of masjid pathok negoro history and atmosphere. The analyzed of virtual experience proved to be advantageous in delivering tangible and intangible information.